Curricular and Administrative Transformation of the Nursing Program at Universidad de Antioquia. 75 Years of History - Posada Vera, Elvigia María; Múnera Gaviria , Hugo Alberto (Investigación y Educación en Enfermería, 2025)
This essay describes the curricular and administrative transformation of the Nursing Program at Universidad de Antioquia since its founding in 1950, identifying progress and challenges up to current times in professional formation, institutional management, and care as disciplinary knowledge. The information has been organized by decades, which evidences historical processes, recognizes change patterns, and highlights relevant milestones more clearly, facilitating a critical analysis of academic evolution in long-term contexts. The institutional trajectory reveals an adaptive capacity regarding social and educational challenges. The most significant milestones include the transition from School to Faculty (1980), the high-quality accreditation from the National Ministry of Education (1999, 2006, 2013, and 2022), incorporation of high technology to teaching (2017), creation of a PhD degree in Nursing (2010), and strengthened work with international networks (as of 2022). These processes have consolidated a critical, humanistic, and socially relevant training in students and graduates. The recovery of this institutional memory strengthens the disciplinary identity and allows projecting a transformative nursing program into the future, committed to academic excellence, social justice, and educational innovation. The historical overview offers tools to address contemporary challenges in health and education, and reaffirms the Faculty’s role as a national benchmark in higher education in nursing.